Functional diversity of 2-oxoglutarate/Fe(II)-dependent dioxygenases in plant metabolism - Farrow, Scott C.; Facchini, Peter J. (Frontiers in Plant Science, 2014)
Oxidative enzymes catalyze many different reactions in plant metabolism. Among this suite of enzymes are the 2-oxoglutarate/Fe(II)-dependent dioxygenases (2-ODDs). Cytochromes P450 (CYPs) as often considered the most versatile oxidative enzymes in nature, but the diversity and complexity of reactions catalyzed by 2-ODDs is superior to the CYPs. The list of oxidative reactions catalyzed by 2-ODDs includes hydroxylations, demethylations, desaturations, ring closure, ring cleavage, epimerization, rearrangement, halogenation, and demethylenation. Furthermore, recent work, including the discovery of 2-ODDs involved in epigenetic regulation, and others catalyzing several characteristic steps in specialized metabolic pathways, support the argument that 2-ODDs are among the most versatile and important oxidizing biological catalysts. In this review, we survey and summarize the pertinent literature with a focus on several key reactions catalyzed by 2-ODDs, and discuss the significance and impact of these enzymes in plant metabolism.